Exploring Students’ Anti-Fraud Awareness: An Empirical Study on Internet Fraud Prevention in Higher Education and Its Implications for Sports Psychology - Peiying Ye; Wufu Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
With the rapid development of the Internet, the diversity of online fraud methods has increased, posing significant risks to college students, who are particularly vulnerable due to limited financial experience and digital literacy. The frequent occurrence of internet fraud in higher education institutions has highlighted the urgent need to enhance students' anti-fraud awareness and implement effective prevention measures. This study focuses on college students from nine higher education institutions in Conghua District, Guangzhou City, employing a combination of qualitative and quantitative methods to explore the factors influencing anti-fraud awareness. A conceptual model of the moderating path of anti-fraud awareness was developed and tested through statistical analysis of five key independent variables: legal knowledge, psychological resilience, ideological education, rights protection awareness, and parental guidance. The study also examines the moderating effect of anti-fraud policies on the relationship between these variables and students’ awareness levels. The findings reveal that psychological resilience and ideological education are particularly influential in fostering anti-fraud awareness, highlighting the importance of integrating these elements into educational and extracurricular programs. These insights have practical implications for anti-fraud initiatives in universities and society at large. Additionally, this research offers valuable perspectives for sports psychology by emphasizing the role of psychological resilience and education in fostering decision-making, risk awareness, and teamwork, which are critical in both academic and athletic contexts.